VZTAH INDEXU EKONOMICKÉ SVOBODY K INDEXU VNÍMÁNÍ KORUPCE - Ševčík, Radim; Vrabec, Michal; Průša, Milan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2007)
The aim of this bachelor work is to estimate the dependency on corruption of economic freedom. Firstly, the theoretical backgrounds of both economical phenomena are examined. Then, the relationship between the economic freedom of the World Fraser Institute and the Corruption Perceptivity Index by Transparency International is discussed, using regression techniques and correlation analysis
Vedoucí práce: Michal Vrabec
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2008
Rok obhajoby 2008
Keywords: mezinárodní ekonomické vztahy [obor disert. práce]; bakalářské práce; bachelor's theses